2016
DOI: 10.1007/s00267-016-0734-y
|View full text |Cite
|
Sign up to set email alerts
|

River Water Pollution Status and Water Policy Scenario in Ethiopia: Raising Awareness for Better Implementation in Developing Countries

Abstract: Despite the increasing levels of pollution in many tropical African countries, not much is known about the strength and weaknesses of policy and institutional frameworks to tackle pollution and ecological status of rivers and their impacts on the biota. We investigated the ecological status of four large river basins using physicochemical water quality parameters and bioindicators by collecting samples from forest, agriculture, and urban landscapes of the Nile, Omo-Gibe, Tekeze, and Awash River basins in Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…In turn, such changes to hydrological and biochemical runoff processes caused by altering spatial pattern (e.g., fragmentation, aggregation, etc.) of riparian forest may have a significant impact on water quality and aquatic biota (e.g., biological diversity and species dynamics) in direct and indirect ways [62][63][64][65][66]. Despite the fact that some studies investigated the effects of riparian forest fragmentation on biological communities in streams [66][67][68], a large portion of the relationship between fragmentation of riparian forests and biological indicators (e.g., diatom, macroinvertebrate, and fish) in streams at riparian scale remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, such changes to hydrological and biochemical runoff processes caused by altering spatial pattern (e.g., fragmentation, aggregation, etc.) of riparian forest may have a significant impact on water quality and aquatic biota (e.g., biological diversity and species dynamics) in direct and indirect ways [62][63][64][65][66]. Despite the fact that some studies investigated the effects of riparian forest fragmentation on biological communities in streams [66][67][68], a large portion of the relationship between fragmentation of riparian forests and biological indicators (e.g., diatom, macroinvertebrate, and fish) in streams at riparian scale remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier studies, good water quality was generally associated with undeveloped watersheds dominated by forest land use, while poor water quality was linked to human development activities, such as agriculture [23]. In the more recent studies, a variety of landscape metrics was used to explain the correlation between landscape patterns and stream water quality, including patch density, largest patch index, landscape shape index or contagion [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of DO in the wet season might be attributed by turbulence of running water, combined with lower content of organic matter in the stormwater runoff, as also suggested in rivers in India and Argentina (Pesce and Wunderlin ; Joshi et al ). The low oxygenation of the river water during dry season, in some samples approaching zero, is ascribed to the organic loads from direct discharge of domestic and industrial wastewater, as also pointed out by Awoke et al () comparing river water quality in four river basins in Ethiopia, and Alemayehu () ascribing low DO in rivers of Addis Ababa from solid waste dumping and wastewater discharge. Furthermore, our finding is consistent with study conducted by Karn and Harada () who reported that the dry season contributed significant impact on river pollution in three urban territories of Nepal, India, and Bangladesh due to year round pollutants flow into the rivers and reduced river water discharge.…”
Section: Discussionmentioning
confidence: 67%